2006
DOI: 10.1167/iovs.05-0757
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PKC   by Oral Administration of Ruboxistaurin Is Well Tolerated and Ameliorates Diabetes-Induced Retinal Hemodynamic Abnormalities in Patients

Abstract: RBX was well tolerated at doses up to 16 mg twice daily for 28 days in patients with diabetes. It ameliorated diabetes-induced RCT abnormalities. No serious safety problems were identified in this patient population. Compared with prior published data, these findings represent the first direct human evidence of both bioavailability of RBX to retinal vessels and amelioration of diabetes-induced retinal hemodynamic abnormalities by an oral PKC beta inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 26 publications
4
77
0
2
Order By: Relevance
“…No significant within-or between-group effects of ruboxistaurin were demonstrated for the remaining efficacy measures. TEAEs were similar between groups, and the adverse event profile was consistent with that previously reported for ruboxistaurin (12,(31)(32)(33)(34)(35).…”
Section: Safety Profilesupporting
confidence: 87%
“…No significant within-or between-group effects of ruboxistaurin were demonstrated for the remaining efficacy measures. TEAEs were similar between groups, and the adverse event profile was consistent with that previously reported for ruboxistaurin (12,(31)(32)(33)(34)(35).…”
Section: Safety Profilesupporting
confidence: 87%
“…The findings reveal a potentially important mechanism of regulation of LXR that warrants further study as abnormal PKC signaling has been observed in diabetes, atherosclerosis, renin expression and glucose metabolism in the liver, all conditions in which LXR is known to play an important role (Collins 2004, Grefhorst et al 2005, Aiello et al 2006, Dey et al 2006.…”
Section: Discussionmentioning
confidence: 91%
“…9,10 Naturally, attenuation of PKC-b activity has been coupled to amelioration of HG-induced retinal and glomerular microvascular complications to which inhibitions of ZO-1 and occludin translocation and the small GTPase RhoA post-translational modification appear to contribute. [11][12][13] It is noteworthy in this context that the increased presence of PKC-b protein has also been documented in the brain infarcts of deceased ischemic stroke patients. 14 Guanosine triphosphate-binding proteins, in particular RhoA, have crucial roles in many cellular processes, including the regulation of endothelial barrier integrity and function.…”
Section: Introductionmentioning
confidence: 85%